Yearbook of the Maimonides Centre for Advanced Studies. 2016 : 2016. - Veltri, Giuseppe. (Jewish Thought, Philosophy and Religion Series, 2016)
The Yearbook of the Maimonides Centre for Advanced Studies mirrors the annual activities of staff and visiting fellows of the Centre as well as scholars of the Institute for Jewish Philosophy and Religion at the University of Hamburg and reports on symposia, workshops, and lectures. Although aimed at a wider audience, the yearbook also contains academic articles and book reviews on scepticism in Judaism and scepticism in general.